If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3r + -4) = -2(4 + -7r) Reorder the terms: 3(-4 + 3r) = -2(4 + -7r) (-4 * 3 + 3r * 3) = -2(4 + -7r) (-12 + 9r) = -2(4 + -7r) -12 + 9r = (4 * -2 + -7r * -2) -12 + 9r = (-8 + 14r) Solving -12 + 9r = -8 + 14r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-14r' to each side of the equation. -12 + 9r + -14r = -8 + 14r + -14r Combine like terms: 9r + -14r = -5r -12 + -5r = -8 + 14r + -14r Combine like terms: 14r + -14r = 0 -12 + -5r = -8 + 0 -12 + -5r = -8 Add '12' to each side of the equation. -12 + 12 + -5r = -8 + 12 Combine like terms: -12 + 12 = 0 0 + -5r = -8 + 12 -5r = -8 + 12 Combine like terms: -8 + 12 = 4 -5r = 4 Divide each side by '-5'. r = -0.8 Simplifying r = -0.8
| -10+2x+40=x+4+2x | | 14=14s | | 9(-4x-5)=99 | | 36x+72=180 | | 182=13x+52 | | log(20x-3)-log(x+4)=2 | | 82=2+30+40a | | 0=b^2+b | | 28s-26=40s-2(2s+5) | | 1m+6=7m | | 4x^2-12x=12 | | 1/4(b+2)=10 | | -3x=-2x+3 | | .25y-.6=.15y+3-.8y | | 2xy-7y=49 | | 5+0.02x=4.69+0.08x | | 1400=10x+500 | | 45=-15+5g | | 2(2m-1)+6(m+2)=8m | | 5f+10=6-3f | | 3s-2=1 | | (x-4)=(2x-7) | | -3k-6=-4k-11 | | 5ng-5n+10ng-20n= | | 0.5x+2x=-50 | | -9+p=-11 | | 8k+3-2k=6 | | 9-8m=-8(m-2) | | 44.79=9g+3.84 | | 23x+33=13x+39 | | 3(2t-1)-7=4(t+1) | | 30-5x=50-13x |